The accessibility of academic study for foreign students. Is the economic viability or national necessary? - Menin, Alon (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
During of these years we see that many public organizations going through changes in economic and perceptual. Among the organizations, we can also discern education and academic organizations. All required processes, efficiency, and profitable economic evidence about the expenditures of the organization. Many countries have found a way of bringing foreign students, a source of economic income turns the wheels of academia, and contributes significantly to the country's existing academic space. Is this global step, like in United States and Australia; are viability and necessary for all the countries? What is the contribution of the foreign student and what benefits it produces? In which level or step are Israel in the economic picture?